Beispiel Nr: 02
$\text{Gegeben:}\\\text{Oberfläche} \qquad O \qquad [m^{2}] \\ \\\text{Grundfläche} \qquad G \qquad [m^{2}] \\ \\ \text{Gesucht:} \\\text{Mantelfläche} \qquad M \qquad [m^{2}] \\ \\ M = O- G \\ \textbf{Gegeben:} \\ O=70m^{2} \qquad G=34m^{2} \qquad \\ \\ \textbf{Rechnung:} \\ M = O- G \\ O=70m^{2}\\ G=34m^{2}\\ M = 70m^{2}- 34m^{2} \\ M=36m^{2} \\\\\\ \tiny \begin{array}{|l|} \hline O=\\ \hline 70 m^2 \\ \hline 7\cdot 10^{3} dm^2 \\ \hline 7\cdot 10^{5} cm^2 \\ \hline 7\cdot 10^{7} mm^2 \\ \hline 0,7 a \\ \hline 0,007 ha \\ \hline 7\cdot 10^{-5} km^2 \\ \hline \end{array} \tiny \begin{array}{|l|} \hline G=\\ \hline 34 m^2 \\ \hline 3,4\cdot 10^{3} dm^2 \\ \hline 3,4\cdot 10^{5} cm^2 \\ \hline 3,4\cdot 10^{7} mm^2 \\ \hline 0,34 a \\ \hline 0,0034 ha \\ \hline 3,4\cdot 10^{-5} km^2 \\ \hline \end{array} \tiny \begin{array}{|l|} \hline M=\\ \hline 36 m^2 \\ \hline 3,6\cdot 10^{3} dm^2 \\ \hline 3,6\cdot 10^{5} cm^2 \\ \hline 3,6\cdot 10^{7} mm^2 \\ \hline 0,36 a \\ \hline 0,0036 ha \\ \hline 3,6\cdot 10^{-5} km^2 \\ \hline \end{array}$